Immuno‑diagnosis of Mycobacterium tuberculosis in sputum, and reduction of timelines for its positive cultures to within 3 h by pathogen‑specific thymidylate kinase expression assays - Wayengera, Misaki; Mwebaza, Ivan; Bayiyana, Alice; Joloba , Moses L. (BMC Research Notes, 2017)
Laboratory diagnosis of Tuberculosis (TB) is traditionally based on microscopy and or culture. Microscopy is however, only sensitive to a specified degree of bacillary load not present in HIV co-infected persons. Traditional cultures of Mycobacterium tuberculosis (M. tb), on the other hand, take weeks to read—thereby delaying the critical decision whether or not, to treat. Although nucleic acids amplification tests (NAATS) applied directly on sputum or cultures can increase the sensitivity for TB diagnosis among those with HIV co-infection as well as reduce time-lines for positive culture detection, they do not replace the need for smear microscopy and culture. We have previously proposed the M. tb DNA-synthetic enzyme thymidylate kinase (aka TMKmt) as an organism-specific growth and proliferation biomarker to reduce time-lines for detection of positive TB cultures. In this study, we explored the secretory levels of TMKmt in M. tb cultures and sputum, towards improving the overall laboratory diagnosis of TB. Modelling of TMKmt secretion in vitro was done by cloning, expressing and SDS-PAGE/MALDI-TOF detection of purified recombinant TMKmt in E. coli. TMKmt expression profiling in M. tb was done by qRT-PCR assay of related messenger ribonucleic acids (mRNA) and TMKmt antigen detection by Enzyme linked Immuno-absorbent Assay (EIA) among cultures of a pathogenic wild-type Ugandan strain (genotype 1) alongside the H37Rv laboratory strain. Owing to the high-load of pathogen in-culture, direct EIA on limiting dilutions of sputum were done to examine for assay sensitivity. A rise in TMKmt antigen levels was observed at 3 h post-innoculation among in vitro cultures of E. coli. The 1st of several cyclic spikes in TMKmt mRNA and antigen levels were detected at 2.5 h among in vitro cultures of the pathogenic wild-type Ugandan isolate alongside the laboratory M. tb strain. TMKmt antigen was detected up to between 1 × 10−4–1 × 10−5 (containing 10 and 1 CFUs/ml) dilutions of a microscopically designated 1+ (est. Acid Fast Bacillary load of 1 × 105) patient sample. Detection of TMKmt expressed mRNA and Ag offers us opportune for instant diagnosis of M. tb in sputum, and reduction of timelines for positive pathogen detection in cultures to within 3 h.